A Study on Teaching Effectiveness and Importance of ICT in Teacher Education: Exploring the Role of ICT in Improving Teaching and Learning in Teacher Education (Journal of Advances and Scholarly Researches in Allied Education, 2019)
The present paper will concentrate on ICT incorporation into teaching education, its effect and role in improving the interest in teaching-learning. This paper aims to stress the role of ICT in education for productive education. The building of a stable and productive community needs schooling. The health of community is calculated. In all ways, education empowers the country. Teachers educate by their educational career. Learning is one of the most daunting careers because awareness is constantly evolving and expanding and the new technology allows all teachers to learn how to teach about this technology. What is fresh today will stay new tomorrow, there is no certainty. It will quickly become redundant. Teachers will be supported by ICT to fix this issue. ICT promotes it as the information universe is just a swipe away.